Understanding access to potable water in resettled areas: A case study of the Karachi Divisional Secretariat Division, Kilinochchi - Kirishanthan, P. (University of Colombo, 2017)
Increasing challenges to access potable water have created numerous problems in highly-populated societies. Societies returning to normalcy after the war face unique challenges in this regard. This study explores the challenges faced by the resettled community in accessing potable water for daily consumption in the Karachi Divisional Secretariat area in the Kilinochchi District. The selected area faces a number of challenges to access potable water. The main objective of this study is to study the challenges faced by the resettled households by looking at their potable water consumption patterns after resettlement. Both random and purposive sampling methods were employed to select both the study area (Grama Niladhari Divisions - GND) and the households as sampling units. Of the inhabitants, 106 households were selected from five GNDs. These GNDs were selected as they are the most affected due to a potable water shortage in the area. Questionnaires and structured interviews were used to collect data. Data were analysed using sample statistical methods such as mean and percentage. The findings show that 74% of the households obtain water from dug wells and 26% from tube wells for daily water consumption excluding drinking water. Seventy-six percent of the households depend on the water supply of the National Water Supply and Drainage Board through bowsers for potable water, while others use wells and tube wells. In the dry season, in the absence of drinking water, people have to travel nearly a kilometre to fetch water or buy from sellers. Women hold the key responsibility to collect water. The results of the study clearly show that people in the study area face challenges in accessing potable water. It is, therefore, recommended that providing potable pipe-borne water to every household would be preferable to the existing system.
Keywords: potable water, resettlement, water shortage